2015
DOI: 10.1074/jbc.r115.694661
|View full text |Cite
|
Sign up to set email alerts
|

The Many Virtues of tRNA-derived Stress-induced RNAs (tiRNAs): Discovering Novel Mechanisms of Stress Response and Effect on Human Health

Abstract: In mammalian cells, mature tRNAs are cleaved by stress-activated ribonuclease angiogenin to generate 5-and 3-tRNA halves: a novel class of small non-coding RNAs of 30 -40 nucleotides in length. The biogenesis and biological functions of tRNA halves are emerging areas of research. This review will discuss the most recent findings on: (i) the mechanism and regulation of their biogenesis, (ii) their mechanism of action (we will specifically discuss their role in the protein synthesis inhibition and the intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 97 publications
(124 reference statements)
0
63
0
Order By: Relevance
“…Another way to alter the pool of available tRNAs is by inducing their endonucleolytic cleavage, which occurs under oxidative stress conditions (Thompson and Parker, 2009). tRNA cleavage events give rise to small RNA species that may function as secondary stress signals (Saikia and Hatzoglou, 2015).…”
Section: Chemical Modifications Of Mrna Influence Translationmentioning
confidence: 99%
“…Another way to alter the pool of available tRNAs is by inducing their endonucleolytic cleavage, which occurs under oxidative stress conditions (Thompson and Parker, 2009). tRNA cleavage events give rise to small RNA species that may function as secondary stress signals (Saikia and Hatzoglou, 2015).…”
Section: Chemical Modifications Of Mrna Influence Translationmentioning
confidence: 99%
“…Later on it was shown that tiRNAs inhibit protein synthesis and induce the phospho-eIF2α-independent assembly of stress granules (SGs). The stress-induced tiRs, produced independent of the sex-hormone stimulated pathways, have been implicated by others in translation repression and as anti-apopotic factors, as reviewed in [51]. …”
Section: Biological Function Of Trfsmentioning
confidence: 99%
“…This could be at least in part attributed to tRNA fragments produced most likely by an RNAse processing mature amino‐acylated tRNAs in halves that are abundant in phloem exudates of pumpkin (Zhang et al ., ). Notably, translational inhibition by tRNA halves also is observed in mammalian cell cultures (Thompson & Parker, ; Yamasaki et al ., ) probably caused by interfering with mRNA access to ribosomes (Saikia & Hatzoglou, ; Gebetsberger et al ., ). In higher eukaryotes, tRNA halves are produced by RNAse T2 class RNases that hydrolyze tRNAs in their anticodon loop and play a role in tumour‐induced angiogenesis (blood vessel formation) and developmental switches, and, in most species, are part of general stress responses (Jochl et al ., ; Fu et al ., ; Thompson & Parker, ).…”
Section: Classes Of Phloem Transported Rnas and Their Functionmentioning
confidence: 99%